Budget impact of netupitant/palonosetron for the prevention of chemotherapy-induced nausea and vomiting. (3rd August 2019) - Park, Sang Hee; Binder, Gary; Corman, Shelby; Botteman, Marc
Abstract: Background: Chemotherapy-induced nausea and vomiting (CINV) are among the most common and debilitating side-effects patients experience during chemotherapy, and are associated with considerable acute care use and healthcare cost. It is estimated that 70–80% of CINV could be prevented through appropriate use of CINV prophylaxis; however, suboptimal CINV compliance and control remains an issue in clinical practice. Netupitant/palonosetron (NEPA) is a fixed combination of serotonin-3 (5-HT3 ) and neurokinin-1 (NK1 ) receptor antagonists (RAs), respectively, indicated for the prevention of acute and delayed nausea and vomiting associated with highly emetogenic chemotherapy (HEC) and moderately emetogenic chemotherapy (MEC). Phase 3 clinical trials showed a significantly higher complete response rate in both acute and delayed CINV in chemotherapy-naïve patients receiving NEPA compared to patients receiving palonosetron. Objective: The objective of this study was to estimate the budgetary impact of adding NEPA to a US payer or practice formulary for CINV prophylaxis. Methods: A model was developed to estimate the impact of adding NEPA to the formulary of a hypothetical US payer with 1.15 million members, including 150, 000 (13%) Medicare beneficiaries. The model compared the annual total costs of CINV-related events and CINV prophylaxis in two scenarios: base year (no NEPA) and comparator year (10% and 5% NEPA usage in HEC and MEC patients, respectively). A univariate sensitivity analysis was conducted to explore the effect of variability in model parameters on the budget impact. Results: A total of 2, 021 patients were eligible to receive CINV prophylaxis. With NEPA, CINV prophylaxis costs increased by 0.7% (3, 493, 630 vs 3, 518, 760) while medical costs associated with CINV events decreased by 3.9% (15, 118, 639 vs 14, 532, 442), resulting in a net cost saving of 561, 067 (3.0%) for the health plan (18, 612, 269 vs 18, 051, 202), or 0.04 per member per month. This was equivalent to saving 5, 011 per patient moved to NEPA. Among all 5-HT3 RA + NK1 RA regimens, NEPA was associated with the lowest CINV-related costs, leading to the lowest total cost of care. Conclusions: Adding NEPA to a payer or practice formulary results in a net decrease in the total budget due to a substantial reduction in CINV event-related resource utilization and medical costs, and an increase in pharmacy costs <1%, saving over 5, 000 per patient.